HAJINYA LANSIA DITINJAU DARI PERSPEKTIF BIMBINGAN DAN KONSELING ISLAM - Kholilurrahman Kholilurrahman (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2017)
Hajj is the fifth pillar of Islam. When the first pillar of Islam until the fourth has been done, the Moslem wants to complete the pillar by performing the pilgrimage as the fifth obligation. However, in modern times today, along with the increasing number of hajj quotas, automatically caused the turn period of hajj to be increased as well. In fact, it raises some problems, especially for the elder Hajj pilgrims. This research aims to identify some problems that arise from the preparation of Hajj until the completion of Hajj in the elderly congregation. The problem is studied based on the perspective of Islamic guidance and counseling by using literature review. This research also uses qualitative approach in the form of case study technique. The result, there are some problems of Hajj experienced by the elderly so that it’s needful for assistance and psychological guidance in the implementation of the pilgrimage by the elderly congregation.